Domestic media products’ gender ideology (Herald of Journalism, 2024)
In recent years, Kazakhstan has seen active discussions regarding gender equality and children's rights in the media. A scientific article conducts an analysis of the manifestation of gender ideas in materials published in domestic media.The aim of this research is to determine the level of discussion of gender equality issues in Kazakhstani media and to understand how gender ideologies are disseminated among the audience through the media.Gender ideology is represented in Kazakhstani media through various methods and genres. Films, articles and other media products shape images not only through visual representations but also through text, cultural codes and connotations that influence perception and the formation of public opinion. Therefore, understanding gender ideology is crucial when creating informational products and shaping public opinion. It is also important to study the influence of informational products on the audience.As part of the scientific approach, a textual analysis of media materials was conducted. From 2020 to 2023, research was conducted on gender processes in the republican newspaper "Ulan" and domestic series on the Gakku TV channel, where an analysis of historical, cultural, philosophical, psychological, and comparative aspects was conducted.As a result of the research, it was found that in some media, certain humanitarian and democratic principles of protecting women's and children's rights were violated. This finding underscores the need to form a humanitarian view on the issue of gender equality and to ensure ethical and aesthetic evaluation of informational products.
Keywords: media